Calf management practices, challenges and opportunities in traditional cattle production systems in the Peanut Basin of Senegal - Tebug, Stanly Fon; Kamga-Waladjo, A.R.; Ema, P.J.N.; Muyeneza, C.; Kane, O.; Seck, A.S.; Ly, M.T.; Lo, M. (Springer, 2015)
Calf management in traditional cattle herds in many parts of the tropics receive less attention as compared to immediate income-generating cows or bulls. Information on long-term implications of poorly reared young stock is limited. A study to assess practices, challenges and opportunities during rearing of less than 12-month-old calves in traditional cattle herds in the Peanut Basin of Senegal was carried out. Data were collected on 207 farms through farm visits and completion of a questionnaire. Categorical principal component analysis followed by two-step cluster analysis identified two cattle production systems: livestock based (LB: 47.83 %) and livestock-crop based (LCB, 52.17 %). On average, 2.81 ± 0.15 calves were reared per farm. Calves were weaned at the age of 12.27 ± 0.32 months. A majority of the calves were of indigenous breeds (71.37 %) and were meant to serve as replacement stock (74.23 %). The tropical livestock unit for cattle owned was significantly lower in LB compared to LCB farms (12.71 vs. 18.85). Significantly higher number of farmers owned non-indigenous calves, had clean calf rearing area and reported feed availability in LB farms as compared to LCB farms. A majority of farmers (98.50 %) perceived calf morbidity and mortality as a major challenge in calf rearing. Meanwhile, labour was readily available to assist with calf rearing in 88.24 % of farms in both systems. Capacity building on improve husbandry practices could enhance calf survival and productivity in surveyed farms. Studies to better identify health and feeding constraints of calves will be necessary to define intervention targets.